Motherly Love of the Main Character in Indian Thriller Film “Mom” (2017) - Tira Nur Fitria (LPPM Universitas Advent Indonesia, 2026)
The objective of this study is to describe the representation of motherly love (love a mother as the main character (Devki) to her stepdaughter (Arya) in the film Mom (2017). The author uses descriptive research which is described through the storyline in terms of dialogue and action. The analysis shows that Mother's love is represented in the form of a mother's struggle for her stepdaughter who gets sexual violence and injustice in the law. Devki, a mother wants to avenge all the criminals who have been involved in the abuse of Arya. Arya is not Devki's biological child, but she loves her very much. Devki the mother is willing to play “dirty” and hires a private detective to complete his noble mission, but Devki is not aware of another danger that threatens him. She did various ways to avenge the suffering her daughter experienced from the perpetrators. As a child, we must have often heard stories about her life suffered because of the torture of her stepmother. In this film, we see a woman as a mother with sincere affection. This film proves that not all stepchildren will end up suffering. Devki proves that she is Arya's stepmother, but her love for her daughter is not about blood relations. Although Devki did do wrong, we may have to admit it. A mother's instinct does not know the meaning of her child, adopted child, or stepchild. A person who plays the title of mother sometimes acts out of sanity for the sake of a child, but she proves that a mother will go through all her limitations to give justice and happiness to her child. Devki is willing to risk his life to give a new life to Arya. She tries to return Arya's life and smiles. Devki is an image of the strength of a mother who is full of love from a stepmother towards her stepdaughter.